The validity of balance principle in aesthetics - Maizan Mat Amin; University Putra Malaysia (2003)
Balance is a principle of design that deals with arranging the visual elements in a work of art for harmony of design and proportion. For most of our reading our eyes and minds are most confortable with evenly balanced layouts where the graphics don?t overpower the text and the page doesn?t seem to tilt to one side or the other. But before we indulge our taste buds, we need a good foundation in the basics of balance-what it is and how to achieve it.
Based on related works, this research is to study the validity of the balance principle classification that has been proposed by Nor Anita [ Nor Anita, 2002].
The classification is based on guidelines and literatures of James E. Shuman [James E. Shuman, 1997], Gestalt Design principles [Dempsey Chang et al, 2011] and Ngo et al?s model [D.C.L. Ngo et al., 1998-2001]. Nor Anita has been recommended to classified characteristics of Balance, equilibrium, Symmetry and Homogeneity to balance principle. In general, we explored how to use the Ngo et. Al ?s model to measure and evaluate the aesthetic elements of a screen design. Then, an experiment was conducted to validate the measurement model for balance principle for selected screen designs and to see how consistent they are with respondents? rating.
Thesis (Degree of Master) -- University Putra Malaysia, 2003
Keywords: Universiti Putra Malaysia -- Dissertations; Dissertations, Academic -- Malaysia; Graphical user interfaces (Computer systems); Human-computer interaction